2020
DOI: 10.3389/fonc.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Identification of RNA Editing Through Integrating Omics Datasets and the Clinical Relevance in Hepatocellular Carcinoma

Abstract: RNA editing is a widespread post-transcriptional mechanism to introduce single nucleotide changes to RNA in human cancers. Here, we characterized the global RNA editing profiles of 373 hepatocellular carcinoma (HCC) and 50 adjacent normal liver samples from The Cancer Genome Atlas (TCGA) and revealed that most editing events tend to occur in minor percentage of samples with moderate editing degrees (20-30%). Moreover, these RNA editing prefer to be A-to-I RNA editing in protein coding genes, especially in 3 ′ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
(54 reference statements)
5
17
0
Order By: Relevance
“…9 Taking this into consideration, the 2 known RNA editing types (A-to-I and C-to-U) together accounted for most of the RNA variants during cardiomyocyte differentiation (Table S1), which is consistent with other studies, and A-to-I editing sites showed a disproportionately high percentage. 9,29 In particular, we also confirmed that approximately 79% of the identified A-to-I editing sites have been found in previous studies stored in the RADAR database. These results collectively indicate that the RNA editing sites identified here are credible.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…9 Taking this into consideration, the 2 known RNA editing types (A-to-I and C-to-U) together accounted for most of the RNA variants during cardiomyocyte differentiation (Table S1), which is consistent with other studies, and A-to-I editing sites showed a disproportionately high percentage. 9,29 In particular, we also confirmed that approximately 79% of the identified A-to-I editing sites have been found in previous studies stored in the RADAR database. These results collectively indicate that the RNA editing sites identified here are credible.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, for these approximately 70% gene-shared stage-specific editing sites, we found that they tended to be identified in the same differentiation stages (88.33%, 477/540) with a few exceptions that were identified in different stages (11.67%, 63/540; Figure 5 C; Table 3 ), which is similar to the phenomenon observed in hepatocellular carcinoma. 29 Among these stage-specific and stage-shared editing sites, 171 had at least 1 functional consequence, such as amino acid sequence changes, alternative splicing variations, miRNA-target regulation, and gene expression alterations, as shown in Figure 4 . 11 Ud-specific editing sites were located in regions of NANOG ( Table 3 ), of which 6 have a potential effect on miRNA-target changes and expression changes in NANOG ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude and the biological consequences of A-to-I editing in the majority of cancers remain largely unknown. Advances in high-throughput sequencing and data generation have revealed that RNA editing events are extensive across the human cancer transcriptome, and that the incidence and progression of multiple cancers are associated with some of these events [7,8,[39][40][41]. In the present study, we aimed to assess the impact of RNA editing in thyroid cancer and to identify de novo cancer-related RNA editing sites using next generation sequencing in an ADAR1-knockdown cellular model.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these examples on specific miRNAs, a global analysis of miRNA sequencing data from healthy and cancerous tissues unveiled that miRNA editing is frequently dysregulated in cancer [130,[135][136][137][138][139].…”
Section: A-to-i Editingmentioning
confidence: 99%